The correspondence of Northrop Frye and Helen Kemp, 1932-1939. - Frye, Northrop (Frye, Northrop. Works. 1996, 1996)
Robert D. Denham has collected in these volumes the 266 letters, cards, and telegrams that Helen Kemp and Northrop Frye wrote to each other during the six periods when they were apart, from the winter of 1931-32 until the summer of 1939. The letters form a compelling narrative of their early relationship. They tell of a romance in which two people fall in love, want to get married, and are confronted with obstacles blocking their path, including lack of money and the education they both need to advance their careers. But the story is much more than a romance. The letters reveal Frye's early talent as a writer, illustrating that both the matter and the manner of his criticism had begun to take shape when he was only nineteen. Helen Kemp's expressiveness and intelligence come through clearly in her letters, which were only discovered in 1992. Kemp and Frye share their thoughts on literature, music, religion, politics, education, and a host of other topics. They discuss their alma mater, Victoria College; artists and musicians of Toronto; southwestern Saskatchewan, where Frye spent a summer as a pastor on a United Church circuit; Frye's hometown, Moncton, New Brunswick; and Kemp's neighbourhood on Fulton Avenue in Toronto. We travel with them around the world, from Ottawa to Rome. We see through their eyes the early years of the Co-operative Commonwealth Federation, the struggles of the United Church of Canada, the activities of the Student Christian Movement, the appeal of Communism, the rise of fascism, and the beginnings of art education in the galleries of Canada.